Pengaruh Tingkat Pemahaman Asuransi terhadap Minat Masyarakat dalam Berasuransi Kesehatan (Studi Kasus di Kelurahan Panggung Kota Tegal) - Sri Ratih Handayani; Endang Widowati (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2019)
ABSTRACT The research method used was a case study in Panggung Village, TegalCity, while the data collection method used was a questionnaire. In testing the hypothesis, Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test and Determination Analysis are used.From the results of the analysis, conclusions can be drawn: 1. There is a positive influence on the level of understanding of insurance on people's interest in health insurance in Panggung Village, Tegal TimurDistrict, Tegal City with t=14.625 with a pvalue of 0.000<0.05. 2. Understanding insurance has an influence of 0.601 with a determination of 36.10%, which means that the variation in changes in respondents' interest in health insurance of 36.10% can be explained by variations in changes in the insurance understanding variable. Meanwhile, the remaining 63.90% is explained by other variables outside the research model. Based on the conclusions, it can be implied as follows: 1. TheoreticalApart from being able to empirically prove several previous studies, the results of this research can also provide a theoretical framework regarding the influence of understanding insurance on interest in health insurance. This research has model limitations because it has a determination of only 36.10%, so there is still the possibility of improvement. Recommendations for further research include adding other variables to strengthen the research construct. 2. PolicyHealth insurance managers can increase public interest in insurance by increasing both the quality and quantity of health outreach and promotionactivities. These health outreach and promotion activities need to be carried out to increase public understanding of the importance of health insurance. The results of this research conclude that there is a positive influence on the level of understanding of insurance on people's interest in health insurance in Panggung Village, Tegal Timur District, Tegal City with t=14.625 with a pvalue of 0.000<0.05. Understanding insurance has an influence of 0.601 with a determination of 36.10%, which means that the variation in changes in respondents' interest in health insurance of 36.10% can be explained by variations in changes in the insurance understanding variable. Meanwhile, the remaining 63.90% is explained by other variables outside the research model. A regression coefficient of 0.601 means that every increase in one score on the insurance understanding variable will increase interest in insurance by 0.601. Vice versa, if there is a decrease in one score in the insurance understanding variable, it will also reduce interest in health insurance by 0.601.Keywords: Level of Insurance Understanding, Public Interest in Health Insurance